2023
DOI: 10.1002/hsr2.1711
|View full text |Cite
|
Sign up to set email alerts
|

Prescription patterns in an intensive care unit of COVID‐19 patients in Bangladesh: A cross‐sectional study

Tanvir Rahman,
Md. Saiful Islam,
Shyamjit Paul
et al.

Abstract: Background and AimsTo reduce death rates for critical patients hospitalized in intensive care units (ICUs), coronavirus (COVID‐19) lacks proven and efficient treatment methods. This cross‐sectional study aims to evaluate how physicians treat severe and suspected COVID‐19 patients in the ICU department in the absence of an established approach, as well as assess the rational use of the medication in the ICU department.MethodsBetween June 16, 2021, and December 10, 2022, a total of 428 prescriptions were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Nevertheless, anticoagulant prescriptions on the wards seemed lower than reported in other investigations [13,15]. For instance, a study on COVID-19 in critically ill inpatients from Spain demonstrated that 89.1% received LMWH at hospital admission [15,17].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Nevertheless, anticoagulant prescriptions on the wards seemed lower than reported in other investigations [13,15]. For instance, a study on COVID-19 in critically ill inpatients from Spain demonstrated that 89.1% received LMWH at hospital admission [15,17].…”
Section: Discussionmentioning
confidence: 78%
“…In 2021, a retrospective study conducted in Spain reported that 85% of critically ill patients received a prescription for anticoagulant therapy with enoxaparin as the most prescribed medication [12]. Similarly, a recent investigation reported that anticoagulants accounted for most of the prescriptions performed in suspected and confirmed COVID-19 patients admitted to an ICU [13].…”
Section: Introductionmentioning
confidence: 99%